2011
DOI: 10.1364/ao.50.004755
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of onboard and scene-based methods for Airborne Prism Experiment spectral characterization

Abstract: Accurate spectral calibration of airborne and spaceborne imaging spectrometers is essential for proper preprocessing and scientific exploitation of high spectral resolution measurements of the land and atmosphere. A systematic performance assessment of onboard and scene-based methods for in-flight monitoring of instrument spectral calibration is presented for the first time in this paper. Onboard and ground imaging data were collected at several flight altitudes using the Airborne Prism Experiment (APEX) imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The spectral smile measured in the laboratory does not depend strongly on wavelength. The shapes of in-flight and laboratory measurements of the spectral smile agree well, but the in-flight values are shifted upwards, because the pressure sensitivity of the instrument affects different wavelengths differently [14]. Figure 10b shows the same, but in the along-track direction.…”
Section: Wavelength Shiftmentioning
confidence: 67%
See 1 more Smart Citation
“…The spectral smile measured in the laboratory does not depend strongly on wavelength. The shapes of in-flight and laboratory measurements of the spectral smile agree well, but the in-flight values are shifted upwards, because the pressure sensitivity of the instrument affects different wavelengths differently [14]. Figure 10b shows the same, but in the along-track direction.…”
Section: Wavelength Shiftmentioning
confidence: 67%
“…It measures backscattered solar irradiance in the visible and near-infrared (VNIR) and in the short-wave infrared (SWIR) with a high spatial and spectral resolution (see Table 1 for spectrometer characteristics). The instrument is calibrated regularly in ground calibration facilities [12,13], and an in-flight calibration facility can be used before and after data acquisition to improve the spectral calibration using a quartz tungsten halogen lamp and four spectral filters [14]. D'Odorico et al [14] determined APEX's spectral calibration parameters for different flight altitudes, i.e., different temperature and pressure conditions, using oxygen and water absorption lines, thus focusing on the near-and short-wave infrared.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral shifts of APEX have previously been analyzed based on spectral features of both the internal in-flight calibration facility and the atmosphere during imaging runs [12]. However, these methods can only provide shift estimates at selected spectral bands where absorption features occur.…”
Section: B Spectral Shift Characteristicsmentioning
confidence: 99%
“…It has already been shown that APEX experiences spectral shifts during in-flight conditions, mainly brought about by changes in pressure and hence related to the operational altitude [11,12]. In the following, any constellation of environmental parameters leading to spectral misregistration will be termed a spectral shift condition.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the hypothesis that the artifact was created due to spectral shifts that were shown to occur during flight operations, largely explained by flight altitudes [5,6], in combination with the spectral characteristics of the dichroic coating.…”
Section: Introductionmentioning
confidence: 99%